(untitled) (Research, Society and Development, 2022)
Due to the epidemic of obesity in the world, the number of bariatric surgeries has increased at an exponential rate, and un increase in number of surgical complications related to accompanies the process, such as anastomotic ulcer, one of the main associated complications. Therefore, highlighting complications such as the formation of marginal ulcers from gastric bypass bariatric surgery is necessary to reduce post-surgical morbidity and mortality. Thus, the overall objective of this study is to analyze the relationship between gastric bypass and the formation of marginal ulcers, as well as to discuss the treatment for this problem. This is an integrative literature review, and the following databases were used for the research: National Library of Medicine National Institutes of Health (PubMed) and Virtual Health Library (BVS/MEDLINE). The screening process relied on the following inclusion criteria: articles that answered the research question, in English, Portuguese and Spanish and that were published between 2017 and 2022. As a result, a total of 12 studies were obtained. For the writing of the discussion, four thematic axes were divided, the first being the pathophysiology of marginal ulcer due to bypass, reported a process of mucosal ischemia and inflammatory process that when associated with the release of gastrin due to vagal stimulation in some patients, generates an acidity environment conducive to ulceration formation. The second topic reported the factors that influence the formation of marginal ulcer, being divided into surgical and non-surgical, among the non-surgical are the irrational use of NSAIDs and infection by H. pylori. The third topic reported the clinical picture and complications of the anastomotic ulcer, among them being hemorrhage, stenosis, malignancy or perforation. Finally, the fourth topic approached the management of marginal ulcer comparing surgical revision with omental repair.